2019
DOI: 10.3390/ijms20040809
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-766-3p Contributes to Anti-Inflammatory Responses through the Indirect Inhibition of NF-κB Signaling

Abstract: MicroRNA (miRNA) is small RNA of 20 to 22 nucleotides in length and is stably present in plasma. Regulating the expression of miRNA taken into cells has been suggested as a general therapeutic approach. We identified the novel anti-inflammatory miRNA hsa-miR-766-3p and investigated its biological function in human rheumatoid arthritis (RA) fibroblast-like synoviocyte MH7A cells. To verify the function of the miRNA present in the plasma of RA patients, we performed a comprehensive analysis of the miRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
(34 reference statements)
0
34
1
Order By: Relevance
“…The most highly up-regulated candidates in COVID-19 patients were miR-31-5p (associated with in ammatory disorders [18][19][20] ) (Figure 1a), miR-3125 and miR-4742-3p, while the most down-regulated were miR-1275 (Figure 1a), miR-3617-5p and miR-500b-3p. The most statistically signi cant change was seen in miR-766-3p (Figure 1a), a known anti-in ammatory miRNA 21 . Unsupervised analysis of variance using principal components analysis (PCA) involving the 55 DE miRNAs showed tight clustering of patient groups (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most highly up-regulated candidates in COVID-19 patients were miR-31-5p (associated with in ammatory disorders [18][19][20] ) (Figure 1a), miR-3125 and miR-4742-3p, while the most down-regulated were miR-1275 (Figure 1a), miR-3617-5p and miR-500b-3p. The most statistically signi cant change was seen in miR-766-3p (Figure 1a), a known anti-in ammatory miRNA 21 . Unsupervised analysis of variance using principal components analysis (PCA) involving the 55 DE miRNAs showed tight clustering of patient groups (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Other patient cytokine data is shown in Supplementary Table 2. One signi cantly reduced miRNA, miR-766-3p, has been shown to reduce IL-6 expression in a dose-dependent manner 21 , while another, miR--4662a-5p (Figure 1c), is predicted to target IL-6 mRNA (TargetScan, release 7.2) 22 . The miRNAs may play a role in the hyperin ammatory state commonly seen in patients with COVID-19 23 .…”
Section: Resultsmentioning
confidence: 99%
“… hsa-miR-361 Overexpression in cutaneous leishmaniosis lesions, impairs epidermal barrier function by filaggrin-2 repression [ 96 ]. hsa-miR-766 Indirectly inhibits of NF-κB signaling causing anti-inflammatory response [ 97 ]. hsa-miR-769 Expression is significantly correlated with the presence of pronounced coronary atherosclerosis [ 98 ], inhibits colorectal cancer cell proliferation and invasion by targeting HEY1 (downstream effector of NOTCH signaling pathway) [ 99 ], negatively correlated with EGFR expression [ 100 ].…”
Section: Abdominal Aorta Aneurysm and Control Groups Constructionmentioning
confidence: 99%
“…Previous studies have reported differences in the expression levels of miRNAs in the peripheral blood of patients with stroke compared with healthy individuals ( 33 , 34 ). In addition, an increasing number of studies have demonstrated that certain miRNAs may exert important cerebroprotective effects against IRI ( 35 , 36 ). miR-766-5p has been reported to exert anti-inflammatory effects on human rheumatoid arthritis fibroblast-like synoviocyte MH7A cells ( 37 ).…”
Section: Discussionmentioning
confidence: 99%